Innovative two-stage thermal control of DC-DC converter for hybrid PV-battery system - Rasool M. Imran; Kadhim Hamzah Chalok; Siraj A. M. Nasrallah (AIMS Electronics and Electrical Engineering)
A photovoltaic (PV)-based generator is a crucial component of modern electricity grids. Most PV systems utilize various maximum power point tracking (MPPT) algorithms to inject the maximum available power into the utility. However, on sunny days, consistently obtaining maximum power can lead to increased thermal stress and a reduced reliability of the power electronic-based DC-DC converter. This paper presents a thermal model for the DC-DC converter that evaluates the accumulated temperature based on power losses and ambient temperature sensed by the thermal sensor. A thermal control strategy is suggested to maintain the temperature of the converter's main components within allowable limits. The thermal control includes two stages: a primary stage that adjusts the switching frequency of the IGBT switches to decrease the accumulated temperature and a secondary stage that adjusts the current-based MPPT algorithm to reduce the maximum current through the main switch. This approach aims to extend the lifespan of the utilized DC-DC converter and lower its operational cost. Furthermore, the allowable range for switching frequency variation is determined through a stability analysis of the frequency response, which is evaluated using a Bode plot for the closed-loop system. The proposed thermal control was implemented in a MATLAB/Simulink environment. The associated results demonstrate the effectiveness of the proposed control in maintaining temperature within acceptable limits and thereby improving the reliability of the system.